(untitled) (Plant Tissue Culture and Biotechnology, 2016)
Attempt was made to produce transgenic cell lines of flax cv. Blanka tolerant to drought stress. Genetic transformation systems were used to incorporate the DREB2A gene, as the specific gene for drought stress tolerance. In biolistic transformation, hypocotyl segments were bombarded with DREB2A and GFP genes at particle flight distance of 9 cm and rupture disc pressure of 1300 psi. The expression of the gene was observed under a light microscope after 24 and 48 hrs. In Agrobacterium?mediated transformation, the hypocotyl segments were incubated overnight with Agrobacterium culture at five optical density OD600 i.e. 0.2, 0.4, 0.6, 0.8 and 1 for 30 min with occasional stirring. Later, the explants were transferred to a selection regeneration medium supplemented with 50 mg/dm3 hygromycin and 300 mg/dm3 cefotaxime and subcultured every two weeks on a new selection medium. Molecular analysis confirmed the expression of the target DREB2A gene in flax genome. Plant Tissue Cult. & Biotech. 26(2): 197-207, 2016 (December